DISTRIBUSI LOGAM BERAT TIMBAL DI PERAIRAN LAUT KAWASAN PESISIR GRESIK - Nindyapuspa, Ayu; Ni'am, Achmad Chusnun (Al-Ard: Jurnal Teknik Lingkungan, 2017)
The increasing of industrial activity on the Gresik Regency will increase the generated waste. One of the generated waste from industrial activity is hazardous waste which contain Lead (Pb). Pb which are disposed to the environment, especially to the sea, will pollute the environment and endanger the life of marine animals like fishes and other marine biota. Therefore, the research of Pb distribution was conducted on the coastal area of Gresik Regency. Sea water samples were taken from 3 different points, Petrokimia Port, Manyar Sub-regency, and Maspion V Industrial Area. Sampling used purposive sample method and samples were analyzed by AAS. Results showed that the highest Pb concentration at Maspion V Industrial area (0.083 mg/L). Meanwhile the lowest Pb concentration at Manyar Sub-regency (0.021 mg/L). Industrial activity that are conducted at Gresik Regency may generate Pb which can pollute the seawater. Keywords: coastal area, Gresik, hazardous waste, lead, seawater